PERTANGGUNGJAWABAN PUBLIK DAN TINDAK PIDANA KORUPSI - Nurhayati, Ratna; Gumbira, Seno Wibowo (Jurnal Hukum dan Peradilan, 2017)
The purpose of this research was to whether the actions of government (bestuurshandeling) based on its discretion can be classified as a criminal act of corruption or not. The Methodology of this research used juridical doctrinal. The result showed that based on legal frame such as Law of The Administrative Court, Law of ASN, Law of Government Administration and legal doctrines as well as the Decision of the judicial review of the Constitutional Court Number: 25 / PUU-XIV / 2016 responsibility of governmental actions (bestuurshandeling), which comes from discretionary (Freies ermessen) containing elements of abuse of authority resulting state loss but there is no element of corruption such as gratifications, bribe, then it can be accounted for by the administrative sanctions under the Law of Government administration Article 20 (6) and Article 80 paragraph (1) Jo Article 81 paragraph (3) in a balanced and case by case. If there is an element of abuse of authority that resulted in state loss and there are elements of corruption such as gratifications, bribe, then accounted for under the criminal law, especially corruption.Keywords: Public responsibility, corruption, governmental actions (bestuurshandeling), Public discreations (Freies Ermessen)